2018
DOI: 10.1177/1362361318817716
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in cognitive empathy and alexithymia occur independently of executive functioning in college students with autism

Abstract: Reduced empathy and alexithymic traits are common across the autism spectrum, but it is unknown whether this is also true for intellectually advanced adults with autism spectrum disorder. The aim of this study was to examine whether college students with autism spectrum disorder experience difficulties with empathy and alexithymia, and whether this is associated with their cognitive levels of executive functioning. In total, 53 college students with autism spectrum disorder were compared to a gender-matched gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 89 publications
1
17
0
1
Order By: Relevance
“…These ndings suggest that autism is profoundly related to de cits in cognitive empathy, especially perspective-taking ability. In support, previous studies of empathy in ASD suggested that in adults with diagnoses such as Asperger syndrome, there were impairments on the perspective taking scale and de cits trends in the fantasy and empathic concern scales on the IRI [3,8,9,10,11].…”
Section: Discussionsupporting
confidence: 74%
“…These ndings suggest that autism is profoundly related to de cits in cognitive empathy, especially perspective-taking ability. In support, previous studies of empathy in ASD suggested that in adults with diagnoses such as Asperger syndrome, there were impairments on the perspective taking scale and de cits trends in the fantasy and empathic concern scales on the IRI [3,8,9,10,11].…”
Section: Discussionsupporting
confidence: 74%
“…Despite some of these interesting and potentially important findings regarding affective empathy, the inconsistencies within our study and in previous research indicates that it is most prudent to conclude that neither autism, nor alexithymia, are robust predictors of atypical affective empathy, especially when compared to their stronger associations with participant sex and cognitive empathy. This is supported by emerging evidence that, in clinically diagnosed people with ASD, neither autism, nor alexithymia, are associated with affective empathy (Ziermans et al 2018). Our data are therefore not consistent with claims that atypical affective empathy, where observed in ASD, is due to alexithymia (Bird et al 2010).…”
Section: Discussionmentioning
confidence: 80%
“…In a study by Bölte et al ( 2008 ), a small group of adults with autism reported higher levels of experienced arousal when viewing neutral pictures and lower arousal when viewing sad stimuli compared to TD controls, which is suggestive of deviant awareness of emotional arousal in ASD. In line with this notion, studies looking at self-reports of individuals with ASD have found that they are generally less able to identify and describe their own emotions (Dijkhuis et al 2017 ; Hill et al 2004 ; Samson et al 2012 ; Ziermans et al 2018 ). It has also been shown that, compared to TD individuals, adults with ASD report higher levels of negative emotions but similar levels of positive emotions (Samson et al 2012 ) and in children and adolescents with ASD emotion dysregulation appears to be related to all core features of the disorder (Samson et al 2014 ).…”
mentioning
confidence: 95%